2011
DOI: 10.1002/cncr.26094
|View full text |Cite
|
Sign up to set email alerts
|

Increasing accrual in cancer clinical trials with a focus on minority enrollment

Abstract: BACKGROUND: The authors reviewed changes in accrual to cancer clinical trials over the last 2 decades at their institution with a focus on minority participation after the implementation of a community clinical oncology program (CCOP) and an aggressive, education‐orientated minority outreach program (MOP). METHODS: Data on patient enrollment in clinical trials for the years 1988 to 2010 was obtained from the William Beaumont Hospital (WBH) Cancer Clinical Trials Office. The type and number of cancers diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…These findings bring a different dimension to the influence of race and cultural perspective in medical and clinical trial settings. [21,22] The relatively high percentage of enrollment among Black women in our study is consistent with a report by Wendler et al, however given our findings documenting the patient perspective on factors influencing enrollment, this should not be interpreted as evidence that barriers to non-white enrollment no longer exist and can be ignored. [23] It is likely there are culturally influenced issues of perceived benefit or risk of harm playing a role in a patient's decision to enter both this study and, more generally, clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…These findings bring a different dimension to the influence of race and cultural perspective in medical and clinical trial settings. [21,22] The relatively high percentage of enrollment among Black women in our study is consistent with a report by Wendler et al, however given our findings documenting the patient perspective on factors influencing enrollment, this should not be interpreted as evidence that barriers to non-white enrollment no longer exist and can be ignored. [23] It is likely there are culturally influenced issues of perceived benefit or risk of harm playing a role in a patient's decision to enter both this study and, more generally, clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…The PPI interventions were also diverse. Patients and/or members of the public were involved in different activities: eight studies involved patients or lay people in designing recruitment and retention strategies (for example, as community partners, members of a community advisory board, or focus group participants), 34 41 51 55 66 69 75 76 12 studies involved patients or lay people in developing patient-facing information (for example, patient information sheets, multimedia and online interventions, recruitment advertisements, and verbal messaging), 39 41 43 45 49 53 58 59 61 63 66 78 and 10 studies involved patients or lay people in directly recruiting or retaining participants (for example, hiring lay/community workers or asking existing participants to refer friends/relatives). 34 36 46 47 51 60 65 67 72 79 The extent of involvement ranged from one patient advocate acting as a panellist in a one-off educational seminar for recruiting clinicians, 59 to more than 80 people helping to develop a patient friendly online trials registry, 41 42 or community partners initiating and leading their own recruitment strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer-focused PBRNs increase minority participation in cancer clinical trials, facilitate diffusion of innovative therapies, and decrease cancer treatment disparities with the goal of improving cancer care quality. [22][23][24][25][26][27][28][29] As a result, one could expect higher rates of hospice enrollment for patients treated at PBRN practices. However, since PBRN patients are also more likely to participate in clinical trials, this could have a negative impact on end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…37 Ideally, if hospice is presented as acceptable palliative therapy when curative treatment is no longer advantageous and is offered universally, minority patients may be more willing to enroll. 23,[38][39][40] In one study, Keating et al 41 found no difference in hospice enrollment by patient race or marital status in an integrated health care system that offers hospice services to participants. In a different study by Cowall et al 35 hospice enrollment differed on the basis of whether a patient was treated in a teaching or nonteaching hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation